PERANCANGAN SYSTEM INFORMASI PENANGANAN KELUHAN KONSUMEN BERBASIS WEB PADA PT. INDUSTIRA BATU CEPER TANGERANG - Rosmawati Dwi; Sinudarwati Sinudarwati; Fika Regita Trismiyanto (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
PT Industira is one of the companies engaged in manufacturing Disassembly power panel (Disribution Board) for TL lamp lighting. To improve costumer service, PT Industira provides Quality Assurance & Customer Service Team Leader (QA & CS TL) as a container to accommodate various complaints handling provided by consumers. Based on the current system obtained the results that the system there are still some disadvantages are all still done manually that need a more accurate new system that is a web-based consumer complaint information system that uses PHP programming with Notepad ++ and MySql database creation. From the process is generated a web-based consumer complaints system that can reduce the ineffectiveness and inefficiency in the delivery of complaints, grievance shelter, data processing complaints, decision makers to the preparation of complaints so that the entire process of handling complaints properly monitored.